How the Lean Management Decision Influences the Transportation Cost in the Supply Chain? - Tamas Kozak; Radovan Madlenak; Gyorgy Ivan Neszmelyi (Communications - Scientific letters of the University of Zilina, 2020)
The purchase decisions require information on where each phase in aretail supply chain should be placed. The presented method is an integrated tool for retail supply chain totransaction cost optimization. The model does not only present a company-level lean management’s decisions within a supply chain, but it also shows the exact method to optimize the supply chain competitiveness. The allocation model also illustrates how the purchase decisions are allocated for producer, distributor and retail companies. The complexity of the allocation model may be affected by the size of the logistic costs, the algorithm used to calculate the supply chain purchase decisions and the final needs of the customers. The lean management approach could be a redemption to a company, but the results do not help to enhance competitiveness for the whole supply chain in every case. In this paper, a model method is demonstrated that helps to gain benefit of the lowest cost of integrated inventory management decisions. One of the essential parts ofthis research is that not onlythe lean management’ result is considered, but effects of purchase decisions are integrated into the whole retail supply chain, as well. This type ofintegrated approachcan have an exponential impact on profitability on supply chain level effectiveness. In the paper are discussed issues that are important from the perspective of carriers, truck owners and operators, transportation policy makers and shippers. Different capacities of transportation and their costs and performance characteristics from lean aspect are discussed as well.